A study of changes in rent payment and their impact on net income on fieldcrops farms in Bulgaria - Damyan Kirechev (ARPHA Proceedings)
The last two decades have seen an increase in rent payments from tenant farms. High rent prices are affecting farm profits and net income. More resources are leaving the farm to compensate for rented farmland, which reduces profits and slows down farm investment opportunities. The purpose of this study is to analyse and evaluate changes in the cost of rental payments on the formation of net farm income. The object of the study is farms specialised in the fieldcrops sector. On the basis of FADN data and using economic and statistical methods, it assesses how the increase in rent payments affects the profits and net income of farms. The results are derived based on the average farm and the median farm in terms of economic size. The net income of small farms is more dependent on rent payments. As the economic size of farms increases, this dependence decreases. There is a strong correlation between net farm income and rent payments. Increasing rent expenditure increases the dependence of net farm income on subsidies.